Textbook on Scar Management State of the Art Management and Emerging Technologies - Téot, Luc (Springer Nature, 2020)
This text book is open access under a CC BY 4.0 license. Written by a group of international experts in the field and the result of over ten years of collaboration, it allows students and readers to gain to gain a detailed understanding of scar and wound treatment - a topic still dispersed among various disciplines. The content is divided into three parts for easy reference. The first part focuses on the fundamentals of scar management, including assessment and evaluation procedures, classification, tools for accurate measurement of all scar-related elements (volume density, color, vascularization), descriptions of the different evaluation scales. It also features chapters on the best practices in electronic-file storage for clinical reevaluation and telemedicine procedures for safe remote evaluation. The second section offers a comprehensive review of treatment and evidence-based technologies, presenting a consensus of the various available guidelines (silicone, surgery, chemical injections, mechanical tools for scar stabilization, lasers). The third part evaluates the full range of emerging technologies offered to physicians as alternative or complementary solutions for wound healing (mechanical, chemical, anti-proliferation). Textbook on Scar Management will appeal to trainees, fellows, residents and physicians dealing with scar management in plastic surgery, dermatology, surgery and oncology, as well as to nurses and general practitioners ; Comprehensive reference covering the complete field of wounds and scar management: semiology, classifications and scoring Highly educational contents for trainees as well as professionals in plastic surgery, dermatology, surgery, oncology as well as nurses and general practitioners Fast access to information through key points, take home messages, highlights, and a wealth of clinical cases Book didactic contents enhanced by supplementary material and videos